Analisis Keberhasilan UMKM Ditinjau dari Literasi Keuangan, Inovasi Produk dan Jiwa Entrepreneur Di Kelurahan Bandar Sono Kota Tebing Tinggi - Indra Welly Arifin; Dedy Dwi Arseto (Sekolah Tinggi Ilmu Ekonomi Bina Karya, 2026)
This study aims to analyze the success of Micro, Small, and Medium Enterprises (MSMEs) in terms of financial literacy, product innovation, and entrepreneurial spirit in Bandar Sono Village, Tebing Tinggi City. This study used a qualitative approach with a descriptive research type. Data were collected through observation, interviews, and documentation involving MSME actors selected using purposive sampling techniques. Data analysis was conducted using the Miles and Huberman model through data reduction, data presentation, and conclusion drawing. The results showed that financial literacy helps business actors manage capital and business cash flow effectively. Product innovation was found to increase product attractiveness and business competitiveness, while entrepreneurial spirit encourages business actors to be more creative, confident, and willing to take risks. The study concludes that MSME success is influenced by the ability to manage finances, create product innovation, and possess a strong entrepreneurial spirit.